Homozygous southeast asian hereditary ovalostomatocytosis: Management dilemma - Asnawi A.W.A.; Sathar J.; Nasir S.F.S.M.; Mohamed R.; Jayaprakasam K.V.; Vellapandian S.T. (John Wiley and Sons Inc., 2024)
[No abstract available]